KAJIAN IRONI DALAM 'DAHAGA' KARYA IVO ANDRI'C - Effendi effendi (Universitas 17 Agustus 1945 Surabaya, 2014)
This paper reports a study on the use of irony in short stories. The focus of the study is irony of situation in Ivo Andri’C’s short story entitled Dahaga. The study adopts qualitative approach since the data are in words or statement. The result of the study shows that the contrasts between the dreams and facts confronted by the two characters in the story, Zhivan, the ring leader and Lazar Zelenovic, the platoon commander, are evidently portrayed and contribute to the excitement of reading the story.